Analisis Perbandingan Pengaruh Pertumbuhan Ekonomi Terhadap Tingkat Kesejahteraan Masyarakat Pada Desa Suralaga Dengan Menggunakan Algoritma Naive Bayes Dan Support Vector Machine (Svm) - Fathurrahman Fathurrahman; Yupi Kuspandi Putra (Fakultas Teknik Universitas Hamzanwadi, 2021)
Data is an inanimate object that is meaningless and useless for anything. This statement is a statement that is not based on existing facts and realities. In principle, data is an inanimate object whose collection can be very influential in all aspects of human life. Data can shock the world if processed and published. Because data is so influential, humans can speak freely which is unlikely to be debated. Data is able to influence the development and progress of a nation in all respects such as: economy, health, policy, security and so on. Therefore, data obtained by means of surveys and so on, must be treated carefully in order to be able to provide maximum contribution in decision making. The search for stable economic growth and environmentally sustainable quality is fast becoming a topical issue among governments, international agencies and other stakeholders interested in sustainable development. The highest accuracy value is shown by experiments using K-Vold Validation 8 and K-Vold Validation 10. While the tolerance given to K-Vold Validation 8 (0.49%) is smaller than K = Vold Validation 10 of (0.58%). This means that K-Vold Validation 8 is tighter than K-Vold Validation 10. So that the best used in decision making is K-Vold Validation 8 at 99.62% with a tolerance of 0.49%. The results of data processing using the Naive Bayes algorithm and the Support Vector Machine both illustrate that the economic influence on the level of welfare of the Suralaga Village community is very large and it can be concluded that the average Suralaga Village community is included in the category of not prosperous. This is indicated by the fact that there are still many people who depend on their livelihoods from working as laborers and foreign workers